THE EFFECT OF APPLYING ORGANIC FERTILIZER ON THE GROWTH AND YIELD OF LAND KALE PLANTS (Ipomea reptans Poir) - Nenden Syolikhat; Herawati Nufus (Sean Institute, 2023)
The increasing demand for vegetables should be offset by an increase in vegetable productivity. To get quality vegetables and optimal yields, fertilization is one of the most important technologies. Fertilization aims to add nutrients to plants so that plants can grow and produce well. The research was carried out on the Agricultural Extension Center (BPP) land in Ciruas District, Serang Regency, Banten, from October 2022 to November 2022. Tillage is carried out by making beds measuring 2.5m long and 0.5m wide as 4 beds. The treatment is K0 for applying Urea and Organic Fertilizer, K1 for applying Organic Fertilizer, and K2 not being given any fertilizer. There was no noticeable difference in the percentage of kale plant growth between the treatments tested. However, the highest percentage growth was obtained in the K0 treatment (29.2) and the lowest in the K2 treatment (22.9). The high percentage of plant growth is due to the kale seedlings used quite well and the planting media also supports the occurrence of plant germination and growth. There is a noticeable difference in yield. The most yields obtained in the K0 treatment (6.3kg) differed markedly from the K1 (4.7kg) and K2(3.7kg) treatments.